Digital Transformation of Human Resources: Strategies for Survival and Competitiveness in the Society 5.0 Era at PT Maxride Makassar - Andi Munawwarah Rusli; Akhmad; Muchriady Muchran; Muhammad Rusydi; Andi Jam’an (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze human resource digital transformation as a strategy for organizational survival and competitive advantage in the Society 5.0 era at PT MaxRide Makassar. The research focuses on understanding and implementing human resource (HR) digital transformation, examining its impact on employee performance and organizational competitiveness, exploring the role of HR training and development, and identifying HR adaptation strategies in response to rapid technological change. The study is motivated by the increasing competition in the transportation and digital platform service industry, which requires companies to continuously adapt by leveraging digital technologies while strengthening the quality and capabilities of their human resources. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, direct observations, and document analysis. Informants were selected using the snowball sampling technique, involving management personnel, employees, and driver partners of PT MaxRide Makassar. The collected data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that digital transformation at PT MaxRide Makassar has positively contributed to improving work efficiency, service responsiveness, system transparency, and employee productivity. Digitalization has enabled work processes to become more efficient, structured, and data-driven, thereby enhancing the company's operational effectiveness. However, the implementation of HR digital transformation has not yet reached its full potential due to several challenges, including disparities in digital competencies, employee resistance to organizational change, insufficient training and development programs, and limitations in technological infrastructure and network connectivity. The study concludes that HR digital transformation at PT MaxRide Makassar has significantly contributed to improving organizational efficiency and competitive advantage. Nevertheless, its long-term success requires greater investment in human resource development, the cultivation of a supportive organizational culture, and the adoption of a human-centric digital transformation strategy to ensure sustainable implementation and strengthen business resilience in the digital era.